Public hearings on the choice of termination of pregnancy : a case of Limpopo Provincial Legislature - Harmse, Jocelyn Lavern (University of Limpopo, 2014)
The aim of the study was to determine whether Members of the Limpopo Provincial Legislature misrepresented members of the public in the policy and decision making process. The Choice on Termination of Pregnancy Amendment Act, No. 213 of 2008, when passed in Parliament, might have had good intensions, but has instead led to unintended consequences. Both qualitative and quantitative research methods were used in this study. Questionnaires were used to collect the primary data from MPLs, staff of the Limpopo Legislature and members of the public in districts of the Province while the secondary data was collected from online databases and through literature reviews. A random sampling method was used to collect primary data for this research by using various data collection methods such as questionnaires, face to face and telephone interviews. The collected data was captured in Ms Excel 2007, and then analysed and presented using graphs and tables. Results of this study indicate that the majority of people in Limpopo were not in favour of the bill in question. This was evident in the video recording that was taken at the public hearing held in the Vhembe District where the emotions and expressions including the language used by members of the public was witnessed. The Committee Report that was tabled in the House by the Chairperson of the Committee stated that all districts in the Province were not in favour of the bill. It also became evident that indeed MPLs did not debate the report in the House and also did not consider inputs of the masses made during public hearings before a provincial mandate was given to Permanent delegates at the National Council of Province (NCOP) to vote in favour of the bill. It can thus be concluded that MPLs can take a decision on a bill even if the masses are against it. This clearly indicates that the voices of the people are indeed heard since public hearings are conducted, but all is merely done to comply with the Constitutional mandate.
Thesis (MPA.) -- University of Limpopo, 2014
Keywords: Public participation; Termination of pregnancy; 361.2100968; Public administration -- Citizen participation -- South Africa -- Limpopo; Political participation -- South Africa -- Limpopo; Abortion -- Government policy -- South Africa -- Citizen participation